Exploring the potential of genebank collections to address food system challenges - McCouch, Susan; Hearne, Sarah Jane; Wenzl, Peter (2023)
This information session will showcase the latest thinking from CGIAR and the Crop Trust about how the genetic diversity of crops conserved in genebanks can be used for the benefit of smallholder farmers the world over.